'We must name ourselves': ERI construction within the supplementary schooling context. (2nd January 2023) - Simon, Amanda
ABSTRACT: Ethnic and racial identity (ERI) has long been considered a central component of psychological wellbeing, particularly for adolescents and young people from Black and minority ethnic (BME) communities. Supplementary schools are geared towards the cultivation of positive group identification and a sense of belonging; central components of ERI. These institutions therefore have a potentially vital role to play in facilitating the wellbeing of the BME young people they serve. Within current literature, there has been very little direct reference to this promotion of wellbeing within supplementary schooling. This paper addresses this dearth by exploring the identity work carried out by a diverse cohort of supplementary schools in the UK. Drawing on in-depth qualitative interview data gathered from the leaders of 16 schools, representing several different BME groups. The data was analysed using thematic analysis and revealed that schools facilitate positive group identity and a sense of belonging through several means, namely: the preservation and perpetuation of emblematic identity traits, the counteraction of negative identity discourses, the transformation of community social standing and the recovery of depleted or lost identities.